Translating Idiomatic Expressions: An Attempt to Raise the Students' Pragmatic Awareness - Izzati Gemi Seinsiani (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2024)
This research aimed to analyze the use of idiomatic expression as a translation activity to increase the students’ pragmatic awareness. Idiomatic expressions were used as the exercise materials since the expressions contain cultural content that needs to be translated appropriately based on context, therefore, the learners have an opportunity to explore the use of the idiomatic expression in its natural situation. This research applied the descriptive qualitative method to analyze the data and describe the finding. The data used were the translation result of 70 English Department Students who took English-Indonesian Translation Course at Universitas Negeri Semarang. They were given two translation exercises containing sentences with idiomatic expressions taken from Crazy Rich Asians Novel. The students had to translate the sentences from English to Indonesian. Then, the results of the students’ exercises were compared to comprehend the learners’ pragmatic awareness. The result proved that there was an improvement after they were given the activities as well as explicit explanations about the meaning and the appropriate use of idiomatic expressions, it showed that their awareness of the idiomatic expressions had increased and as a result, they have a better understanding of the use of the idiomatic expressions in everyday life.